EFFECT OF LIQUEFIED PETROLEUM GAS PRICE ON THE LEVEL OF PATRONAGE AMONG HIGHER EDUCATION STUDENTS (UNIZIK Journal of Marketing, 2025)
This paper examined the effect of prices of LPG fuel, LPG cylinders, and LPG accessories on the patronage and use of LPG for cooking by students of higher education institutions (HEIs) in Lagos State. The paper is necessary because of the benefits of switching to a clean cooking fuel like LPG by students of HEIs in Nigeria and the important role of price in achieving this. The target population was the students of the Faculty of Science, University of Lagos. The research used a cross-sectional design and convenience sampling technique. A structured questionnaire was used to collect data from a valid sample of 250 respondents from University of Lagos, Akoka. A multiple regression statistical method was used to test the hypotheses. Results from the analysis suggested that prices of LPG fuel and cylinders did not significantly affect the patronage and use of LPG for cooking by the students of HEIs. On the contrary, the findings indicated that prices of LPG accessories significantly affected LPG patronage and use. It was concluded that prices of LPG fuel, LPG cylinders, and LPG accessories affected LPG patronage differently. The research also made recommendations. Finally, the research limitations and suggestions for future studies were provided.
Keywords: Price, liquefied petroleum gas, cylinders, accessories, cooking, and customer patronage.